Production scientific on the evaluation of children’s vision: a bibliometric study in the database LILACS - Pinheiro, Raquel Cristina (2012)
This study aimed to perform bibliometric analysis of scientific literature on evaluation of vision available in the database Lilacs. The research methodology has observed the following steps: review of literature on the evaluation of vision and bibliometrics, collection of data in the database Lilacs, organization, processing and bibliometric analysis of data collected using the software MS Excel. Using the search terms “visual assessment”, “assessment of vision”, “functional assessment of vision”, “visually impaired”, “low vision” and “disorders of vision”, being selected 27 articles. As a results were produced the following indicators: the predominant languages of scientific productions were Portuguese and Spanish, the original article written in co-authorship is the predominant type of publication, the themes discussed were: low vision, visual acuity, amblyopia and glaucoma. It was also noted that not all authors have specifically or on assessments of vision, and proposed the cognitive assessment and quality of life of visually impaired. It is advisable to conduct further research to demonstrate the importance of early assessment of vision in children, to ensure that the intervention, when necessary, take place as soon as possible and prevent the delay caused by visual impairment. It should also ensure that these visual findings are complementary with assessments that characterize situations in which individuals who already have some type of disability can use their vision more effectively